PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF DENGAN APLIKASI ADOBE FLASH CS6 UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA KOMPETENSI DASAR MENGANALISIS PERAN, FUNGSI DAN MANFAAT PAJAK (Studi Kasus Siswa Kelas XI IPS 1 MAN 1 Jember Semester Genap Tahun Ajaran 2016 - Sofiyatul Hidayah; Sri Wahyuni; Hety Mustika Ani (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2017)
This research was a classroom action research (CAR) consists of two cycles. Each cycle consists of planning, action, observation and reflection. The purpose of this study was : (1) described the use of interactive learning media with Adobe Flash CS6 applications in improving students' motivation to the basic competence in analyzing the role, functions and benefits of tax class XI IPS 1 MAN 1 Jember 2ⁿᵈ Semester Of Academic Year 2016 / 2017, (2) determined the increase motivation to learn class XI IPS 1 Jember through the use of interactive learning media with Adobe Flash CS6 application to the basic competence to analyze the role, functions and benefits of tax in 2ⁿᵈ Semester Of Academic Year 2016/2017. The subjects research were students of class XI IPS 1 MAN 1 Jember which amount 30 students. Source data was gained from teachers and students. Data collection techniques were observation of students’ motivation and interview to teachers and students after using the media. Data analysis technique in this study was using descriptive qualitative data analysis. The results showed that: The motivation of students in the first cycle increased to 3.04 in the high category. However, there were indicators of students' motivation in middle category, so we need second cycle. In the second cycle students' motivation rise 3.54 in the high category and all indicators of student motivation were also at a high category. The conclusion of this study was the use of interactive learning media with Adobe Flash CS6 applications can increase students' motivation in class XI IPS 1 MAN 1 Jember on basic competence in analyzing roles, functions and benefits of tax in 2ⁿᵈ semester of academic year 2016/2017.